2013
DOI: 10.1136/gutjnl-2013-305763
|View full text |Cite
|
Sign up to set email alerts
|

Risk of new or recurrent cancer under immunosuppressive therapy in patients with IBD and previous cancer

Abstract: Patients with IBD with a history of cancer are at increased risk of developing any (new or recurrent) cancer, with a predominant incidence of new cancers. Treatment with immunosuppressants has no overall major impact per se on this risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
98
2
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 130 publications
(107 citation statements)
references
References 18 publications
5
98
2
2
Order By: Relevance
“…The first data came from Beaugerie et al [12], who reported on the effect of IMS treatment in a cohort of 405 patients with a prior cancer who were included in the CESAME study. Of these patients, 260 had been diagnosed with a cancer more than 2 years prior to enrollment and 145 within 2 years of enrollment in the study.…”
Section: Are Ibd Patients With a Previous Malignancy At Risk Of Develmentioning
confidence: 99%
See 2 more Smart Citations
“…The first data came from Beaugerie et al [12], who reported on the effect of IMS treatment in a cohort of 405 patients with a prior cancer who were included in the CESAME study. Of these patients, 260 had been diagnosed with a cancer more than 2 years prior to enrollment and 145 within 2 years of enrollment in the study.…”
Section: Are Ibd Patients With a Previous Malignancy At Risk Of Develmentioning
confidence: 99%
“…Recent reports have also associated thiopurines with an increased risk of all-cause malignancies in IBD [7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26]. Incorporation of 6-TGN nucleotides in the DNA and RNA is responsible for induction of both remission of disease and mutagenesis and cancer promotion.…”
Section: What Are the Potential Carcinogenic Properties Of Ims Used Imentioning
confidence: 99%
See 1 more Smart Citation
“…In recent data from the prospective French CESAME cohort, the overall incidence of cancer was significantly higher in patients with previous cancer when compared with patients without a history of cancer, with a multivariate-adjusted hazard ratio of 1.9 (95% CI: 1.2-3.0, p = 0.003) [15]. Importantly, among patients with a prior history of malignancy, there was no significant difference in the actuarial probability of remaining free of cancer recurrence or new cancer according to exposure to any immunomodulator at cohort entry.…”
Section: Cancer Risk In Patients With Previous Cancermentioning
confidence: 99%
“…It could be difficult in some situations, such as occurrence of ipsilateral subsequent breast cancer, to differentiate cancer recurrence from development of a new tumor [15]. …”
Section: Cancer Risk In Patients With Previous Cancermentioning
confidence: 99%